1985
DOI: 10.1159/000158598
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Involution and Physiological Death of Smooth Muscle Cells of Rat Incisal Arterioles

Abstract: The sequential morphology of vascular smooth muscle cell involution and physiological cell death was studied by electron microscopy on rat incisors. Concurrently with changes in the pulp of the continuously growing incisor, its arterioles pass through a cycle of growth, remodeling, regression and decay. During the cycle, smooth muscle cells of the arterioles were observed to involute by segregation of cytoplasmic components, formation of autophagic and digestive vacuoles and shedding of cell fragments. Phagocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Necrosis or accidental type of cell death, initially described as a distinct subgroup of cell death, can be recognized as a terminal stage of apoptosis and autophagy. Morphological studies of cell death in tissue revealed that different forms of cell death may occur simultaneously (Thorball et al 1985, Anglade et al 1997. Moreover, dying cells may share apoptotic and autophagic features (Ômixed type' of cell death) (Bursch et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Necrosis or accidental type of cell death, initially described as a distinct subgroup of cell death, can be recognized as a terminal stage of apoptosis and autophagy. Morphological studies of cell death in tissue revealed that different forms of cell death may occur simultaneously (Thorball et al 1985, Anglade et al 1997. Moreover, dying cells may share apoptotic and autophagic features (Ômixed type' of cell death) (Bursch et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is not only an important physiological process during embryonic development, but it is thought to play an important role in the pathophysiology and treatment of many diseases, such as cancers (Kerr, Winterford, and Harmon 1994). As for blood vessels, apoptosis has been found only, so far, in neonatal lamb arteries (Cho, Courtman, and Langille 1995) and human incisal arteries (Thorball, Moe, and Winther-Nielsen 1985). Evidence has been accumulating, since 1994, to suggest that apoptosis probably occurs in hypertension (Devlin et al 2000), peripheral and coronary atherosclerosis (Geng and Libby 1995), and cystal medial degeneration and aortic dissection (Ihling et al 1999).…”
mentioning
confidence: 99%
“…It may be that the stresses of serum deprivation and the other processes involved in preparing a highly concentrated graft cell suspension (TC) trigger autophagic graft cell death. Cells that undergo autophagic cell death may be cleared by phagocytosis 122124 in a process that limits inflammatory and immunological responses 125 . Consistent with these features of autophagic cell death, there was clear evidence of graft engulfment by macrophages and neutrophils in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%